Colors associated with styles of love - Félix Neto (2002)
Colors associated with different love attitudes were examined using the Hendrick and Hendrick Love Attitudes Scale for six love styles. 143 college students rated the extent to which each love style reminded them of 12 colors. As expected, Lee's representation of the love-color analogy was not supported. Each love attitude was associated with relatively distinct colors.